Implications of Sign Language Systems on Academic Performance in English for Learners with Hearing Impairment in Special Secondary Schools in Kenya - Nyongesa, Gregory Jumah (JOOUST, 2024)
Students with Hearing Impairment (HI) face challenges in the process of learning. These students have continued to perform below average in Kenya Certificate of Secondary Education (KCSE). Explanations regarding this performance have pointed to Sign language systems of instructions, proficiency of learners with HI in English, teaching and learning strategies as well as perspectives of the learners with HI and the Special Educators towards the sign systems that are used. This study examined the sign language systems used during English lessons and their implications on academic performance of students with HI. The objectives of the study were to: Examine the sign language systems used for instruction, determine the perspectives of teachers of English (ToE) and learners with HI towards the sign systems, Establish the influence of students with HI proficiency in Sign systems on academic performance in English and find out the teaching and learning strategies employed during English lessons and their implications on academic performance. The study adopted multiple case study design within a qualitative approach. The study was conducted in four special secondary schools for learners with HI in Nyanza region of Kenya with a sample size of 48 participants which included; 33 form 3 students, 7 ToE, 4 Curriculum Support Officers and 4 Principals. Purposive sampling technique was used to select four schools while saturated sampling technique was used to select 7 ToE. Stratified sampling was used to select 33 Form 3 students. The study employed in-depth interview schedules, focus group discussions, Classroom Observations and a document analysis guide as the research tools. University Supervisors validated research instruments. Thematic analysis was employed for data analysis based on the themes that emerged. The findings indicated that three sign systems; Signed Exact English (SEE), Signed English (SE) and Kenyan Sign Language (KSL) are used during English lessons. Every school and ToE decide which system to use. There is no policy for sign language systems. Sign system used during instruction has a direct impact on the performance of learners in English. The study also established that many ToE prefer to use SEE during English lessons. Students with HI prefer KSL to SEE. It was also established that Students with HI are proficient in KSL than SEE and that they comprehend content faster when taught in KSL than in SEE. However, KSL affects them in writing English exams. There was consensus that SEE is the appropriate sign system to be used during English lessons since it helps the students with HI in writing English Exams although KSL makes them comprehend content faster than SEE. Pre-lingual learners are more proficient in KSL than SEE and SE. The post-lingual students are more proficient in SEE as compared to KSL. Students with HI who are proficient in SEE perform well in English as compared to KSL. The students with HI who are post-lingual have better vocabulary than the pre-lingual. KSL knowledge by learners with HI cannot help them pass English. Methods used for instruction include; note taking, questioning technique, incorporation of ICT, Use of visual aids, dramatization, group discussions, lecturing, singing, use of peer tutoring and team teaching. Group discussion and peer tutoring are the preferred approaches. The study recommends; a policy to have SEE used for teaching English, KSL be offered as a teaching subject in Universities for Bachelor’s degree in Special needs Education, English lessons be scheduled in the morning, syllabus for students with HI be modified to suit the needs and interests of the learners, Concepts that are abstract to student with HI be removed from the syllabus, Students with HI be provided with dramatized set books in signs, ToEs to focus on learner centered methods, the learners be exposed story books, newspapers, group discussions and peer tutoring.
Keywords: Sign Language Systems; Academic Performance in English; Learners with Hearing Impairment; Special Secondary Schools; Kenya